Interventions of an Academic Medical Center to Improve Likelihood to Recommend. Issue 3 (July 2015) - Dunham, Daniel P.; Alcorn-Kell, Nancy
<x xml:space="preserve">Abstract</x> Improved patient satisfaction is correlated with improved adherence and health outcomes for patients and financial performance for health care organizations. Increasingly, efforts are being made to measure and optimize patient satisfaction by both providers and insurers. Researchers investigated whether specific changes in staff interaction with patients would improve patients' likelihood to recommend a practice. There were 4 separate initiatives implemented by the medical staff and providers at 14 unique practice sites. At these sites, patients' satisfaction was measured 9 weeks prior to the initiative and then for 9 weeks after to assess impact on patients' likelihood to recommend the practice. Each of the 4 initiatives demonstrated improved patient satisfaction, whereas 2 reached statistical significance. These interventions demonstrated a rise in likelihood to recommend the practice score from 78.6% (33rd percentile) to 83.1% (68th percentile) in all of the combined practices.